Topics in Igneous Petrology - Ray, Jyotisankar; Sen, Gautam; Ghosh, Biswajit; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2011)
The second half of the past century witnessed a remarkable paradigm shift in approach to the understanding of igneous rocks. Global literature records a change from a classical petrographic approach to emphasis on mineral chemistry, trace element characteristics, tectonic setting, phase relations, and theoretical simulation of magma generation and evolution processes. This book contains contributions by international experts in different fields of igneous petrology and presents an overview of recent developments. This book is dedicated to the late Dr Mihir K. Bose, former professor of the Department of Geology, Presidency College, Calcutta, India, who actively participated in the development of this new global view of igneous petrology. Audience: This book will be valuable for scientists and researchers working in igneous petrology and geochemistry.
Foreword -- Acknowledgments -- List of contributors -- 1. A review of the radiometric data placing the Hawaiian-Emperor Bend at 50Ma; placing constraints on hypotheses concerning the origin of the Hawaiian-Emperor Volcanic chain -- 2. Giant plagioclase basalt from northern part of Jhabua District, Madhya Pradesh, Central India -- 3. Occurrence and origin of scapolite in the Neoproterozoic Lufilian-Zambezi belt, Zambia: Evidence/role of brine-rich fluid infiltration during regional metamorphism -- 4. New seismic evidence for the origin of arc and back-arc magmas -- 5. Polybaric evolution of the volcanic rocks at Gabal Nuqara, northeastern desert, Egypt -- 6. Geochemical and geochronological data from charnockites and anorthosites from India's Kodaikanal-Palani Massif, Southern Granulite Terrain, India -- 7. Petrological evolution and emplacement of Siwana and Jalor Ring Complexes of Malani Igneous Suite, Northwestern Peninsular India -- 8. Deccan Traps Flood Basalt Province: an Evaluation of the Thermochemical Plume Model -- 9. Recycling of flow-top breccia crusts into molten interiors of flood basalt lava flows: Field and geochemical evidence from Deccan Traps -- 10. Upper Triassic Karmutsen formation of Western Canada and Alaska: A plume-generated oceanic plateau formed along a mid-ocean ridge nucleated on a late Paleozoic active margin -- 11. Mineral compositions in the Deccan igneous rocks of India; an overview -- 12. The intra-oceanic Barren Island and Narcondam arc volcanoes, Andaman Sea: Implications for subduction inputs and crustal overprint of a depleted mantle source -- 13. Geology, petrology and geochemistry of the volcanic rocks of the Axum area, northern Ethiopia -- 14. Textural fingerprints of magmatic, metamorphic and sedimentary rocks associated with the Naga Hills Ophiolite, Northeast India -- 15. Geological and geochemical studies of Kolekole cinder cone, Southwest Rift Zone, East Maui, Hawaii -- 16. Petrogenesis of flood basalts of the Narsingpur-Harrai-Amarwara-Lakhnadon section of Eastern Deccan Province, India -- 17. Age and origin of the Chilka anorthosites, Eastern Ghats, India: Implications for massif anorthosite petrogenesis and break-up of Rodinia -- 18. Kimberlites, supercontinents and deep Earth dynamics: Mid-Proterozoic India in Rodinia -- Subject Index.
Keywords: Geography; Geochemistry; Earth Sciences; Geochemistry